Aplicação de doses de silicato de potássio para a redução da severidade da brusone em plantas jovens de trigo - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The Pyricularia oryzae pathogen causing blast of wheat is responsible for losses in production, which can reach more than 50% in the crop. As alternative to the use of chemical defenses to wheat diseases control, the use of silicate products has presented satisfactory results in the reduction of both biotic and abiotic stress. The objective of this work was to test the efficiency of potassium silicate doses in reducing the blast severity on young wheat plants and to evaluate the mycelial growth of the fungus P. oryzae in vitro, submitted to the same doses of potassium silicate. The experiments were conducted in a greenhouse and at the Phytopathology Laboratory, Federal University of Pampa. In the greenhouse, BR18, BRS208, BRS Louro cultivars were seeded in 0.4 kg pots, with five replicates per treatment, and six plants per replicate. The design was a completely randomized. The experiment was repeated twice. At 28 days after sowing the plants were sprayed with potassium silicate (g / L): 0; 5; 10; 20 and 25 doses. Twenty-four hours (h) after application of the product, the plants were inoculated with a suspension of 10^4 conidia / mL. After inoculation, the plants remained in the mist chamber for 24 h, with a temperature of 26 ± 2 ºC and relative humidity of 80%, in the absence of light. Subsequently, the photoperiod was restored (12h). In the in vitro experiment the doses were incorporated in BDA medium (potato, dextrose and agar) and conditioned in Petri dishes. In the center of the plate were patched mycelium discs of the pathogen 0.5 mm in diameter. Plates were placed in growth chambers (BOD) at 28 ° C for nine days. The evaluation of severity in young plants was performed seven days after inoculation, with the aid of a diagrammatic scale. Severity data were submitted to analysis of variance and regression. Mycelial growth was evaluated daily and the Mycelial Growth Rate Index (IVCM) was determined by the current diameter of the colony subtracted from the diameter of the colony of the previous day divided by day of numbers after repication. The IVCM and severity data were submitted to analysis of variance and regression adjustments, using SisVar software. The best dose for BR18 and BRS208 cultivars was 18g / L and for BRS Louro was 16.86g / L. In vitro, all doses of potassium silicate inhibited mycelial growth of P. oryzae, and the 16 g / L dose provided the greatest reduction in IVCM. Potassium silicate is efficient in reducing the blast severity on young plants of wheat, and that the doses of potassium silicate and inhibited the growth of the pathogen in vitro. The use of potassium silicate, in a preventive way, emerges as a possibility of greater protection against foliar pathogens in this crop.
Keywords: Nutrição mineral; Pyricularia oryzae; Triticum aestivum; Mineral nutrition; CNPQ::CIENCIAS EXATAS E DA TERRA